The complete plays of Jean Racine. - Racine, Jean, 1639-1699 (Complete plays of Jean Racine, 2010)
"An English translation, in iambic pentameter couplets, of The Fratricides, a play by seventeenth-century French playwright Jean Racine"--Provided by publisher.